THE DEVELOPMENT OF JUNIOR HIGH SCHOOL MATHEMATICS LEARNING TOOLS USING REALISTIC MATHEMATICS EDUCATION APPROACH TO RELATIONS AND FUNCTIONS MATERIAL - Noviani, Julia; Firmansyah, Firmansyah (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
This study aims to produce learning tools using Realistic Mathematics Education approach to relations and functions material. This type of research used the Plomp development model, which consists of three phases, namely the initial investigation phase, the development or prototyping phase, and the assessment phase. The research subjects were grade VIII students of SMPN 2 Takengon. The instruments of research are expert validation sheets, practicality assessment sheets, and effectiveness assessment sheets. The resulting tools include lesson plan, student books, teacher books, and student worksheets. The average assessment of the four aspects of the lesson plan was 3.89 with valid criteria. The average assessment of the three aspects of the teacher’s book was 3.98 with valid criteria. The average assessment of three aspects of the student book was 3.97 with valid criteria. The average assessment of two aspects on the student worksheets was 3.75 with valid criteria. Learning implementation 96.86% and carried out well. The teacher’s response showed that, on average, 82% of the lesson plan assessment aspects are responded positively by the teacher. The response of student books was obtained by 83.2% of students who gave positive responses to student books and 82.6% of students who gave positive responses to student worksheets. The students’ learning outcomes obtained a classical average value of 74.2. The results of validation and testing of learning tools show that the tools meet the criteria of learning tools developed, referring to valid, practical, and effective.